Brain mechanisms of short-term habituation and sensitization toward dyspnea - Stoeckel, M. Cornelia; Esser, Roland W.; Gamer, Matthias; Büchel, Christian; von Leupoldt, Andreas (Frontiers in Psychology, 2015)
Dyspnea is a prevalent and threatening cardinal symptom in many diseases including asthma. Whether patients suffering from dyspnea show habituation or sensitization towards repeated experiences of dyspnea is relevant for both quality of life and treatment success. Understanding the mechanisms, including the underlying brain activation patterns, that determine the dynamics of dyspnea perception seems crucial for the improvement of treatment and rehabilitation. Towards this aim, we investigated the interplay between short-term changes of dyspnea perception and changes of related brain activation. Healthy individuals underwent repeated blocks of resistive load induced dyspnea with parallel acquisition of functional magnetic resonance imaging data. Late vs. early ratings on dyspnea intensity and unpleasantness were correlated with late vs. early brain activation for both, dyspnea anticipation and dyspnea perception. Individual trait and state anxiety were determined using questionnaire data. Our results indicate an involvement of the orbitofrontal cortex, midbrain/periaqueductal gray and anterior insular cortex in habituation/sensitization towards dyspnea. Changes in the anterior insular cortex were particularly linked to changes in dyspnea unpleasantness. Changes of both dyspnea intensity and unpleasantness were positively correlated with state and trait anxiety. Our findings are in line with the suggested relationship between the anterior insular cortex and dyspnea unpleasantness. They further support the notion that habituation/sensitization towards dyspnea is influenced by anxiety. Our study extends the known role of the midbrain/periaqueductal gray in anti-nociception to an additional involvement in habituation/sensitization towards dyspnea and suggests an interplay with the orbitofrontal cortex.